2016
DOI: 10.1038/srep34012
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic insight into the norepinephrine-induced fibrosis in systemic sclerosis

Abstract: Raynaud’s phenomenon is frequently observed in systemic sclerosis (SSc) patients, and cold- or stress-induced norepinephrine (NE) has been speculated to be associated with vasoconstriction. Objective was to elucidate the role of NE in fibrosis in SSc. IL-6 is a potent stimulator of collagen production in fibroblasts. NE enhanced IL-6 production and proliferation more significantly in SSc fibroblasts than in normal fibroblasts. Furthermore, the production of IL-6 and phosphorylation of p38 in SSc fibroblasts wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 46 publications
(53 reference statements)
0
12
0
Order By: Relevance
“…IL‐6 signaling is also recognized as being involved in the development and progression of fibrosis in SSc . Expression of mRNA for type I collagen and IL‐6 in the lungs of MFG‐E8 –/– TSK/+ mice was significantly higher than that in the lungs of MFG‐E8 WT TSK/+ mice (Figure H).…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…IL‐6 signaling is also recognized as being involved in the development and progression of fibrosis in SSc . Expression of mRNA for type I collagen and IL‐6 in the lungs of MFG‐E8 –/– TSK/+ mice was significantly higher than that in the lungs of MFG‐E8 WT TSK/+ mice (Figure H).…”
Section: Resultsmentioning
confidence: 96%
“…Western blot analyses were performed according to previously described protocols . To examine the effect of rMFG‐E8 on TGFβ‐ or latent TGFβ–induced fibrosis–related protein expression in SSc fibroblasts, the cells were pretreated with rMFG‐E8 (100 ng/ml) for 1 hour and then stimulated with TGFβ1 (2 ng/ml) or latent TGFβ (2 ng/ml) for 48 hours.…”
Section: Methodsmentioning
confidence: 99%
“…We previously reported that phosphorylation of p38 was involved in the mechanism of the production of IL-6 in SSc fibroblasts (Uehara et al, 2016). Therefore, we next examined the phosphorylation of p38 in SSc fibroblasts treated with ATP.…”
Section: Atp-induced Il-6 Production In Ssc Fibroblasts Was Mediated mentioning
confidence: 98%
“…ATP-induced IL-6/IL-6 receptor trans-signaling increased the production of collagen type I in SSc fibroblasts IL-6 trans-signaling is mediated in IL-6 receptore nonexpressing cells, including fibroblasts and ECs, by a complex of IL-6 and soluble IL-6 receptor through gp130 (Kawaguchi et al, 1999;Khan et al, 2012). Several studies reported that the complex of IL-6 and soluble IL-6 receptor increased the production of collagen type I in SSc fibroblasts in vitro (Kawaguchi et al, 1999;Uehara et al, 2016). At first, we confirmed that IL-6 receptor was not expressed in SSc fibroblasts and SSc fibroblast-conditioned medium without adding recombinant IL-6 receptor (rIL-6R) (Figure 4e).…”
Section: Atp-induced Il-6 Production In Ssc Fibroblasts Was Mediated mentioning
confidence: 99%
See 1 more Smart Citation